Gestión de almacenes y competitividad en la Municipalidad Provincial de Ucayali Contamana, 2024 - Echevarria Pasmiño, Gustavo (2025)
The final report aimed to determine the relationship between warehouse management and competitiveness in the Provincial Municipality of Ucayali Contamana, 2024. Choosing a sample of 142 workers, who were given a questionnaire to collect information. The results show that warehouse management is regular with 27%, this evaluation is mainly due to the fact that, in most cases, goods and materials arrive in good condition to the warehouse. On the other hand, competitiveness is regular (28%), this is because the institution sometimes meets the deadlines established for its activities and achieves favorable results in them. However, it almost always contributes to the achievement of the strategic objectives of the institution. Finally, it was determined that there is a strong positive correlation between warehouse management and competitiveness, contrasted by a Rho coefficient of 0.824 and a p value of 0.000.